ChemInform Abstract: Enzymatic Transformations Involved in the Biosynthesis of Microbial Exo‐Polysaccharides Based on the Assembly of Repeat Units. Issue 28 (July 2015) - Schmid, Jochen; Sieber, Volker
Abstract Review: 74 refs.